Gereja dan Korupsi: Analisis Isi Khotbah (Content Analysis) Terkait Praktek Korupsi di Papua - Hendrik Vallen Ayomi; PRT. Paramma (Komisi Pemberantasan Korupsi, 2021)
If the Church is perceived as a moral institution, then this institution should play a greater role in fighting corruption. However, the facts show the opposite which until now Papua is included in the list of the top ten most corrupt provinces, even though more than 80% of the population claims to be Christian. This study uses a content analysis approach. Researchers reduced the findings based on four levels categories, namely the equivalent word category, cognitive, affective, and conative. The results of this study indicate that the attention of church leaders to corruption issues is not a top priority.